PENTAGRAM: FROM COMPLEXITY TO EMOTION THROUGH SOFTWARE SEQUENCERS - Yudhistira, I Gede Raditya; Putra, I Pt. Lukita Wiweka Nugraha (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Pentagram investigates the integration of technology in modern music composition, focusing on the use of software sequencers to merge human creativity with machine precision. The study highlights how these tools transform live performance by enhancing technical and expressive dimensions. The research aims to explore the roles of sequencers in Pentagram, focusing on complex pattern execution, real-time effect manipulation, expressive outcomes, and the intricate communication between the musician and the sequencer. This study employs a qualitative descriptive approach with a focus on music analysis, examining how sequencers contribute to technical precision, real-time responsiveness, and emotional storytelling in live performances. The research demonstrates that sequencers enable complex pattern execution, real-time effect manipulation, and intricate communication between the musician and the sequencer, offering new possibilities for composition and live performance. Pentagram highlights the transformative potential of sequencers in music, showcasing their ability to expand creative boundaries by combining precision, expressiveness, and innovation in live performance.